2017
DOI: 10.1038/s41598-017-05820-0
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-tagged Chikungunya Virus Replicons Improve Visualisation of Non-Structural Protein 3 by Fluorescence Microscopy

Abstract: Chikungunya virus (CHIKV), a mosquito-borne alphavirus, causes febrile disease, muscle and joint pain, which can become chronic in some individuals. The non-structural protein 3 (nsP3) plays essential roles during infection, but a complete understanding of its function is lacking. Here we used a microscopy-based approach to image CHIKV nsP3 inside human cells. The SNAP system consists of a self-labelling enzyme tag, which catalyses the covalent linking of exogenously supplemented synthetic ligands. Genetic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 84 publications
4
42
0
Order By: Relevance
“…In cells transfected with full-length nsP3, nsP3 co-localized with G3BP1, but not with eIF3b in the majority of cells examined (73%; Fig. 1a, c), as previously reported [36,42]. In contrast, in cells transfected with the nsP3 HVD alone, the nsP3 HVD co-localized with both SG components eIF3b and G3BP1 in 93% of cells examined (Fig.…”
Section: In Untransfected Cells Eif3b and G3bp1supporting
confidence: 85%
See 3 more Smart Citations
“…In cells transfected with full-length nsP3, nsP3 co-localized with G3BP1, but not with eIF3b in the majority of cells examined (73%; Fig. 1a, c), as previously reported [36,42]. In contrast, in cells transfected with the nsP3 HVD alone, the nsP3 HVD co-localized with both SG components eIF3b and G3BP1 in 93% of cells examined (Fig.…”
Section: In Untransfected Cells Eif3b and G3bp1supporting
confidence: 85%
“…S1c). Taken together with work from others [36,[40][41][42], these data suggest that expression of full-length nsP3 alters the association of individual SG components (e.g., release of eIF3b and retention of G3BP1 with nsP3), and it is likely that domain(s) other than HVD of nsP3 may be responsible for suppressing SG formation.…”
Section: In Untransfected Cells Eif3b and G3bp1supporting
confidence: 61%
See 2 more Smart Citations
“…Instead a significant reduction in total infectious viral titer was observed in Aedes albopictus in vivo [195]. Interestingly, Remenyi and colleagues also showed that nsP3 is closely associated with the host cellular lipid droplets and also with nsP1 [196].…”
Section: Nonstructural Protein 3 (Nsp3)mentioning
confidence: 99%